HUBUNGAN PARITAS,USIA PERKAWINAN DENGAN RESIKO LESI PRAKANKER SERVIKS PADA PASANGAN USIA SUBUR - Sofia Mawaddah; Ivanna Dwi Susanti (MMJ (Mahakam Midwifery Journal), 2020)
Abstract Background:Risk factors that support cervical cancer at the age of marriage, the younger sexual intercourse the more risk of cervical cancer. Women actively engaging in sexual relations and changing partners are also risk factors for cervical cancer.Objective:To determine the relationship between parity and age of marriage with the risk of cervical precancerous lesions in WUS.Method:Analytic with correlation study through cross sectional approach.This research was conducted in Petuk Bukit Kelurahan with sample of 35 respondents obtained by consecutive sampling method. The population of all women is fertile in area of ​​Petuk Bukit village. The bivariate analysis used in this study is the Chi Square statistical test.Results:From the results of the examination obtained 19 positive respondents IVA and 16 negative respondents IVA. The results of the statistical test were obtained the p-Value of parity from 1,000 (α <0.05) and the p-Value of marital age was 0.033 (α <0.05) with OR = 0.129 meaning that mothers who married at age ≥20 years have risk of 0.129 times cervical precancerous lesions compared to married mothers age of ≤20 years.Conclusion: There is a relationship between marital age and the risk of precancerous cervical lesions in mothers of fertile age couples. Keywords: IVA, marital age, precancerous cervical lesions